2018
DOI: 10.11648/j.aff.20180701.13
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Host Density and Viability on Superparasitism Behavior of <i>Trichogramma cacoeciae</i> and <i>T. principium</i> Females

Abstract: Non-choice laboratory experiments were conducted to estimate the influence of host density and viability of codling moth eggs on the superparasitism behavior of Trichogramma principium Sug. et Sor and T. cacoeciae Marchal (Hymenoptera: Trichogrammatidae). There was a strong effect of number of emerged offspring of T. principium and T. cacoeciae and host density on the mean number of parasitized eggs. The tendency of T. principium and T. cacoeciae females to oviposit was increased when high number of Cydia pomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A series of factors (e.g., host exposure time, host density, female mating status) affect self‐superparasitism in wasps (Darrouzet et al, 2003; van Nieuwenhove et al, 2012; Kraft & van Nouhuys, 2013; Nalini, 2015; Harba & Idris, 2018). Our study showed that female age did not affect self‐superparasitism, which agrees with Michaud & Mackauer (1995), who found that older virgin females did not have more self‐superparasitism than younger virgin females.…”
Section: Discussionmentioning
confidence: 99%
“…A series of factors (e.g., host exposure time, host density, female mating status) affect self‐superparasitism in wasps (Darrouzet et al, 2003; van Nieuwenhove et al, 2012; Kraft & van Nouhuys, 2013; Nalini, 2015; Harba & Idris, 2018). Our study showed that female age did not affect self‐superparasitism, which agrees with Michaud & Mackauer (1995), who found that older virgin females did not have more self‐superparasitism than younger virgin females.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, insects are becoming resistant to insecticides over time and help to produce superbugs [19]. Hence, nding control methods for P. operculella becomes increasingly important to continue in growth and development of the potato industry [36,17].…”
Section: Introductionmentioning
confidence: 99%
“…Trichogramma species (Hymenoptera: Trichogrammatidae) are important biological control agents of agricultural pests (Woelke et al, 2017) and have more than 400 host species, especially Lepidoptera (Harba & Idris, 2018). The success of egg parasitoids in the field is closely associated with their search capacity (Siqueira et al, 2011), which is mainly mediated by chemical stimuli from hosts (Strand & Vinson, 1982; Vinson, 1998).…”
Section: Introductionmentioning
confidence: 99%